2004
DOI: 10.1073/pnas.0304797101
|View full text |Cite
|
Sign up to set email alerts
|

Saccharomyces cerevisiae Sin3p facilitates DNA double-strand break repair

Abstract: There are two main pathways in eukaryotic cells for the repair of DNA double-strand breaks: homologous recombination and nonhomologous end joining. Because eukaryotic genomes are packaged in chromatin, these pathways are likely to require the modulation of chromatin structure. One way to achieve this is by the acetylation of lysine residues on the N-terminal tails of histones. Here we demonstrate that Sin3p and Rpd3p, components of one of the predominant histone deacetylase complexes of Saccharomyces cerevisia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
114
2

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(126 citation statements)
references
References 58 publications
10
114
2
Order By: Relevance
“…In addition, RPD3 deacetylates lysine 16 on histone H4 in the vicinity of a DSB that can only be repaired by NHEJ. Consequently, RPD3 mutants also disrupt NHEJ, indicating that HDAC activity is also involved in the NHEJ-mediated DSB repair [59]. Time-course chromatin immunoprecipitation data suggest that HDACs are involved in restoring chromatin to its original conformation during the final steps of the DSB repair process [60].…”
Section: Hdaci and Double Strand Break Repair Machinerymentioning
confidence: 97%
“…In addition, RPD3 deacetylates lysine 16 on histone H4 in the vicinity of a DSB that can only be repaired by NHEJ. Consequently, RPD3 mutants also disrupt NHEJ, indicating that HDAC activity is also involved in the NHEJ-mediated DSB repair [59]. Time-course chromatin immunoprecipitation data suggest that HDACs are involved in restoring chromatin to its original conformation during the final steps of the DSB repair process [60].…”
Section: Hdaci and Double Strand Break Repair Machinerymentioning
confidence: 97%
“…For instance, DNA repair after ultraviolet irradiation is related to acetylation of H3K9 and H3K14 in the affected loci (Yu et al, 2005), and H4K8Ac has been linked to HR of DSB (Downs et al, 2004). Additionally, H4K16Ac was detected at DSB sites in yeast (Jazayeri et al, 2004). Male absent on the first (MOF), the main HAT responsible for H4K16Ac in higher eukaryotes (Dou et al, 2005;Smith et al, 2005;Taipale et al, 2005) that is involved in male dosage compensation in Drosophila (Hilfiker et al, 1997), binds to ataxiatelangiectasia mutated protein (ATM), a kinase that triggers the response to DNA damage in DSB by its phosphorylation of targets involved in DNA repair, cellcycle control and apoptosis (Gupta et al, 2005).…”
Section: Diverse Functions Of Histone H4 Lysine 16mentioning
confidence: 99%
“…Following DNA repair, acetyl marks may be removed (deacetylation) by the action of histone deacetylases. Although such a possibility awaits experimental proof, histone deacetylases were shown to be required for efficient DNA repair (Jazayeri et al, 2004;Tamburini and Tyler, 2005). In addition, it was shown that histone H3 and H4 were acetylated during homology-directed repair and that deacetylation occurs after DNA repair is completed (Tamburini and Tyler, 2005).…”
Section: Dna Repairmentioning
confidence: 99%